2012
DOI: 10.3390/ijerph9020511
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Contamination from Cemetery Soils: Case Study of Zandfontein Cemetery, South Africa

Abstract: The burial of coffins may pose an environmental and health hazard since the metals that are used in coffin-making may corrode or degrade into harmful toxins. These may leach into the surrounding soils and groundwater. Very little research has been conducted world-wide on the mineral contamination potential of cemeteries, and virtually none in South Africa. The aim of the study is to determine whether burial practices affect the mineral content of soils in cemeteries. This was done by comparing the mineral conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 12 publications
0
60
1
2
Order By: Relevance
“…The study further highlighted that arsenic content of the cemetery soils may have been greatly influenced by the practice of embalmment as well as the use of arsenic-sprayed wood for the construction of coffins. A study conducted by Jonker and Olivier (2012) in a South African cemetery revealed a similar pattern of higher onsite mineral contamination, with a decreasing trend offsite. The study highlighted that mineral contamination onsite may have been caused by the discharge and environmental distribution of cemetery leachate over time.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The study further highlighted that arsenic content of the cemetery soils may have been greatly influenced by the practice of embalmment as well as the use of arsenic-sprayed wood for the construction of coffins. A study conducted by Jonker and Olivier (2012) in a South African cemetery revealed a similar pattern of higher onsite mineral contamination, with a decreasing trend offsite. The study highlighted that mineral contamination onsite may have been caused by the discharge and environmental distribution of cemetery leachate over time.…”
Section: Introductionmentioning
confidence: 73%
“…To establish the naturally occurring background soil level for the Murambi site, two topsoil samples were collected from a nearby offsite area. The samples collected from this location were mixed together into one sample to establish an offsite control sample for the soils inside of the Murambi site, similarly described in the work of Jonker and Olivier (2012). The offsite samples were labeled Murambi-Control (BG).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations